A, The Relationship Between Knowledge And Attitudes Of Adolescent Girls With The Dangers Of Pregnancy In Middle Adolescence At Smk Negeri 3 Banjarbaru In 2024 - Anita, Nur; Januarsih, Januarsih; Maslani, Hj. Noorhayati; Rizani, Ahmad (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2024)
Teenage pregnancy is a pregnancy that occurs in a woman under the age of 18 at the time the pregnancy ends. Pregnancy in adolescents can be dangerous if knowledge and attitudes are not monitored. To determine the Relationship between Knowledge and Attitudes of Adolescent Girls with the Dangers of Pregnancy in Middle Adolescence at SMK Negeri 3 Banjarbaru in 2024. This study used analytic observational research with a cross-sectional approach. The population in this study amounted to 153 respondents, who were taken by total sampling technique. The independent variables in the study were knowledge and attitude. The dependent variable in this study is the danger of pregnancy in adolescence. Collection and using a questionnaire. Data were analyzed using Spearman's Rho test with a significance of α = 0.05. The results showed that there was a significant relationship between knowledge and the dangers of pregnancy in middle adolescence (p=0.001; r= -0.256*). There is a significant relationship between attitude and the dangers of pregnancy in middle adolescence (p=0.004; r= -0.192**). The relationship obtained is a fairly strong relationship and the relationship between these variables is not unidirectional, meaning that the better the knowledge of adolescents, the danger of teenage pregnancy can be negative and also positive towards the danger of pregnancy in adolescence and the better the attitude of adolescents, the danger of teenage pregnancy can be negative and also positive towards the danger of pregnancy in adolescence. Keyword : Knowledge, Attitude, Danger Of Pregnancy In Middle Adolescence